Strengthening Mentorship in Global Health for US Medical Students - Olamide Jarrett; Linda Humaidan-Zayed; Stacey Chamberlain; Stevan Weine (Ubiquity Press, 2023)
US medical students demonstrate strong interest in receiving global health training. In 2012, the Center for Global Health (CGH) at the University of Illinois College of Medicine (UICOM) developed a Global Medicine (GMED) program to match this interest. From its initiation, mentorship has been a key component of the GMED program. More recently, this has been strengthened by applying additional evidence-informed approaches toward mentoring. These include the "mentor up" approach, a "network of mentors," and an individualized development plan (IDP). Applying these changes were associated with increases in the number of student abstract presentations and peer-reviewed journal publications. Mentorship based upon evidence-informed approaches should be a key component of global health education in academic medical centers.